Orofacial and cervical myfunctional evaluation pre and post prosthetic rehabilitation (Research, Society and Development, 2020)
Objective: Evaluate in rates the orofacial and cervical myofunctional disorders of adults and older people, also to evaluate the masticatory function before and after prosthetic rehabilitation. Method: It is an intervention study with  quantitative nature, using the e-Myo software for myofunctional assessment associated with the swallowing threshold test to evaluate masticatory function. The study was performed with 20 (twenty) participants, divided into two groups: G1 composed by 10 (ten) adults and G2 composed by 10 (ten) older people, being structured in two stages: in the first stage, myofunctional evaluation and test of the swallowing threshold in the present oral condition; in the second stage, prosthetic recovery was performed with the production of complete and / or partial removable prostheses and, thirty days after the installation of the prostheses, a second myofunctional evaluation was performed, as well as the second swallowing threshold test. Results: Regarding myofunctional assessments, 3 (three) participants in the adult group and 5 (five) in the older people group did not present any change in the general classification rate. 1 (one) participant in the adult group showed a change with a negative impact on the general rate. It was found a reduction in the swallowing threshold in both groups after prosthetic rehabilitation, with higher rates in the adult group. Conclusion: There was a large number of masticatory cycles in patients with fewer dental elements present, with an improvement in the general rate of classification of myofunctional disorders. There was a reduction in the swallowing threshold in the 2 (two) groups after prosthetic rehabilitation, with higher rates in the adult group.